A qualitative study of gendered psychosocial processes in eating disorder development. Issue 7 (24th May 2022) - Springmann, Marie‐Luise; Svaldi, Jennifer; Kiegelmann, Mechthild
Abstract: Objective: Gender and sexual identity constitute social categories that have been found to be important when identifying persons at risk for eating disorders (ED), since prevalence rates are especially high for women as well as persons of gender and sexual minorities. The objective of this study is to enhance the understanding of how these social categories relate to ED development. Method: A qualitative, inductive approach was used in order to develop empirically grounded hypotheses about gendered aspects in ED development. Data are 14 narrative interviews with persons of diverse sexual and gender identities who recovered from anorexia or bulimia nervosa. Interviews were analyzed in depth using Grounded Theory Methodology and Voice Centered Listening. Results: Results suggest that social experiences related to female gender, as well as social experiences related to non‐compliance with social gender norms, can be important for ED development. Those social experiences were described as influencing participants' self‐worth, body image and self‐regulatory strategies, which were connected to ED symptomatology. Discussion: Future research should further validate the gendered aspects presented in this paper, since including a broader array of gendered social aspects in ED research might help to improve etiological understanding and prevention methods. Public Significance Statement: This study contributes a special perspective to research on eating disorders and gender, because it is based on first‐person perspectives of formerly affected persons and integrates the experiences of persons with different gender and sexual identities. Participants described four categories of gendered social experiences relevant for their eating disorders. We discuss the potential of these categories to guide future research on the development of eating disorders and their prevention.